Lasing from micro- and nano-scale photonic disordered structures for biomedical applications - Gayathri, Radhakrishn (2024)
A disordered photonic medium is one in which scatterers are distributed randomly. Light entering such media experiences multiple scattering events, resulting in a "random walk"-like propagation. Micro- and nano-scale structured disordered photonic media offer platforms for enhanced light-matter interaction, and in the presence of an appropriate gain medium, coherence-tunable, quasi-monochromatic lasing emission known as random lasing can be obtained. This paper discusses the fundamental physics of light propagation in micro- and nano-scale disordered structures leading to the random lasing phenomenon and related aspects. It then provides a state-of-the-art review of this topic, with special attention to recent advancements of such random lasers and their potential biomedical imaging and biosensing applications.